Remainder Theorem With Second Degree Divisor

What is the remainder when x2013 is divided by x2– 1? This problem was taken from 2009 MTAP-Dep-Ed Math Challenge Finals. The problem looks very easy but if you don’t know the basic principle how to deal with this problem you can never answer this in just a minute. This article will teach you how to deal with problem like this.

remainder theoremLet :

P(x)     be a polynomial with degree n.

D(x)     be the divisor in second degree.

Q(x)    be the quotient when P(x) is divided by D(x)

R(x)     be the remainder when P(x)     is divided by D(x)

If D(x) is a  1st degree expression, the remainder is constant.

If D(x) is a second degree expression and  the remainder is a in 1st degree expression in the form of Ax+B.

We can say that P(x) = D(x)(Q(x))+R(x)


Worked Problem 1:

What is the remainder when x^2013 is divided by x^2- 1?


P(x)= x^2013                      D(x)= x^2- 1 or (x-1)(x+1)       Required: R(x)



P(x) = D(x)(Q(x))+R(x) x^2013= (Q(x))(x-1)(x+1)+Ax +B

Let x=1 to simplify things out.

(1)^{2013}= (Q(1))(1-1)(1+1)+A(1) +B

1=A+B,   let’s call this equation 1.


Let x=-1

(-1)^{2013}= (Q(11))(-1-1)(-1+1)+A(-1) +B

-1=-A+B let’s call this equation 2.

Solve equation 1 and 2 simultaneously.

A=1 , B=0

Therefore the remainder is 1(x)+0 or x.


Worked Problems 2:

What is the remainder when x^{2014}-2x^{2013}+1 is divided by x^2-2x?



P(x)= x^{2014}-2x^{2013}+1        x^2-2x

P(x) = D(x)(Q(x))+R(x) x^{2014}-2x^{2013}+1= Q(x)(x)(x-2)+Ax+B

Let x=2

(2)^{2014}-2(2)^{2013}+1= Q(2)(2)(2-2)+A(2)+B 2^{2014}-2^{2014}+1= 0+2A+B

2A+B=1,  equation 1


Let x=0

(0)^{2014}-2(0)^{2013}+1= Q(0)(0)(0-2)+A(0)+B 1=B

From equation 1,





The remainder is (0)x+1 or simply 1












Blogger and a Math enthusiast. Has no interest in Mathematics until MMC came. Aside from doing math, he also loves to travel and watch movies.

Latest posts by Dan (see all)

You may also like...

2 Responses

  1. Ula says:

    Hi, i think that i saw you visited my website thus i came to “return the favor”.I’m trying to find things to enhance my site!I suppose its ok to use a few of your ideas!!

  2. Hello there! Do you know if they make any plugins to help with SEO? I’m trying to get my blog to rank for some targeted keywords but I’m not seeing very good results. If you know of any please share. Kudos!

Leave a Reply

Your email address will not be published. Required fields are marked *